PENERAPAN HAK EX OFFICIO HAKIM DALAM PERKARA CERAI TALAK (Studi Putusan Pengadilan Agama Kabupaten Malang Nomor 3645/Pdt.G/2019/Pa.Kab.Mlg) (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
AbstractOne of the talak divorce cases in the Malang District Religious Court is decision number 3645 / Pdt.G / 2019 / PA.Kab.Mlg during the process of examining the case especially in giving a ruling, the judge may not give a ruling beyond what is demanded in the petition. On the other hand, the judge has ex officio rights, namely the judge's authority because of his position, so that the judge can give obligations to the husband to fulfill the rights of the divorced wife even though in the petitum the petition is absent. However, the judge sentenced the Petitioner to charge a mut'ah income of Rp. 6,000,000 to the applicant (his wife). The purpose of this study is (1) To describe the consideration of judges in the application of ex officio rights in divorce divorce case number 3645 / Pdt.G / 2019 /PA.Kab.Mlg. (2) To describe the review of positive law and Islamic law in the application of the right of ex officio judge divorce divorce case number 3645 / Pdt.G /2019/ PA.Kab.Mlg. this research uses qualitative research with descriptive research type.Keywords: Implementation, Ex Officio Judge Rights, Talak Divorce.